I do belive that answers are:
derivative: sin(6θ) = 6cos(6θ)
derivative: 1/sin^3(θ) = -3cos(θ)/sin^4(θ)
2007-03-23 19:49:24
·
answer #1
·
answered by sam b 5
·
0⤊
0⤋
ok, so for this question, you have to use the chain rule. Basically, this says that du/dt = du/dv * dv/dt
I will start with sin6theta. (I'm going to assume this is sin (6theta) instead of (sin^6) theta for the first part. I will also use 't' instead of 'theta' because its shorter)
So assign the variable u to equal sin (6t), and the variable v = 6t. So then u would equal sin v.
Now you want to find du/dt, which is equal to du/dv * dv/dt.
u = sin v, so du/dv is equal to cos v.
v = 6t, so dv/dt = 6.
So then du/dt = 6*cosv. Now you have to put the v=6t back in the u equation and you will get:
du/dt = 6*cos (6t).
[If the question was (sin^6) t, then you would set v = sin t, and then u would be v^6 since sin^6 t = (sin t)^6.
So then du/dt = du/dv * dv/dt, and du/dv = 6v^5 and dv/dt = cos t, so then du/dt = 6v^5 * cos t = 6 sin^5 t * cos t.]
For the second part, you can change 1/(sin^3 t) to sin^(-3) t. and to almost the same thing. Set v = sin t and u = sin^(-3) t = v^(-3).
du/dv = -3*v^(-4); dv/dt = cos t,
du/dt = -3*cos t * v^-4 = -3*cos t * (sin t)^(-4) = -3 cos t / sin^4 t
Hope that helped.
2007-03-24 02:55:42
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
1) f(t) = sin(6t). By the chain rule,
f'(t) = 6cos(6t)
2) f(t) = 1/[sin^3(t)]
By identities, since sin(t) = 1/csc(t), csc(t) = 1/sin(t).
f(t) = csc^3(t)
f'(t) = 3[csc^2(t)] [-csc(t)cot(t)]
Which simplifies as
f'(t) = -3 csc^3(t)cot(t)
2007-03-24 02:51:45
·
answer #3
·
answered by Puggy 7
·
0⤊
0⤋
Question 1
y = sin 6Ã
let u = 6Ã so y = sin u
du/dà = 6
dy/du = cos u = cos 6Ã
dy / dà = (du/dÃ).(dy/du) = 6.cos.6Ã
Question 2
y = sin^(-3)Ã = (sinÃ)^(- 3)
dy/dà = (-3).sin^(-4).Ã.cos Ã
dy/dà = (-3).cosà / sin^(4)Ã
2007-03-24 05:52:24
·
answer #4
·
answered by Como 7
·
0⤊
0⤋